Perilaku Merokok di Dalam Rumah dan Kejadian Penyakit Tuberculosis Paru Sebagai Sumber Pembelajaran - Siska Wulandari; Aseptianova Aseptianova; Saleh Hidayat (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2018)
This research is motivated by smoking behavior in the house with the incidence of pulmonary tuberculosis. The formulation of the problem in this research is How the smoking behavior in the house and the incidence of pulmonary tuberculosis disease as a source of a learning. The purpose of this research was to determine of smoking behavior in the house with the incidence of the pulmonary tuberculosis disease as a source of a learning. Research method is used descriptive qualitative. Population and sample in this research is community in outbreak region 3-4 Ulu Palembang which is patient with tuberculosis lung disease based on data obtained from puskesmas 4 Ulu Palembang on between 2016 and 2017 and from doctor practice in region of 3-4 Ulu Palembang. Data collection techniques in this study using a questionnaire, while data analysis techniques using statistics descriptive. Based on the results of research and discussion of research, description of smoking behavior in the house and the incidence of pulmonary tuberculosis is true and done by respondents in Village 3-4 Ulu Palembang which is a patient of pulmonary tuberculosis disease obtained from the primary data in this study and it can be concluded that the behavior of smoking in the house can cause epidemic pulmonary tuberculosis disease although there are also respondents who are not active smokers but they are exposed to pulmonary tuberculosis disease which is probably caused by anything else obtained from the secondary data in this study.